Physics for scientists and engineers a strategic approach - Knight, Randall Dewey (Pearson Education, Inc., 2015)
For the Fourth Edition of Physics for Scientists and Engineers, Knight continues to build on strong research-based foundations with fine-tuned and streamlined content, hallmark features, and an even more robust MasteringPhysics program, taking student learning to a new level. By extending problem-solving guidance to include a greater emphasis on modeling and significantly revised and more challenging problem sets, students gain confidence and skills in problem solving. A modified Table of Contents and the addition of advanced topics now accommodate different teaching preferences and course structures